Case Report: Multimodality evaluation and clinical management of a single coronary artery - McAlpin, Patrick; Purlee, Matthew; Dickey, Ann; Chandran, Arun; Al-Ani, Mohammad Ahmad Zaki (Frontiers in Cardiovascular Medicine, 2024)
A 14-year-old male with no significant medical history presented with intermittent palpitations for 2-3 months that occurred at rest and were associated with light-headedness. Electrocardiogram in clinic showed sinus arrhythmia with early repolarization and no ischemic changes. The echocardiogram showed normal cardiac structure and function, however, there was a concern for possible anomalous origin of the left coronary artery (Figure 1).Contrast-enhanced CT coronary artery angiogram confirmed a single coronary origin from the right coronary sinus. The single main coronary artery gave rise to the right coronary artery (RCA) and the left coronary artery (LCA). The LCA demonstrated a trans-septal course before it gave rise to the left anterior descending and left circumflex artery (Figures 2 and 3). There were intraarterial and intramural portions of the LCA, and the sinoatrial node artery arose from the LCA (Figure 4). The RCA demonstrated a normal course to the right atrioventricular groove, and the posterior descending artery arose from the RCA. Treadmill exercise stress test showed excellent functional capacity without exercise-induced chest pain or ischemic ECG changes. Invasive coronary angiography ruled out luminal narrowing or dynamic compression. Given the absence of physiologic or anatomic evidence of coronary flow restriction, no intervention was pursued and the palpitations were deemed to be likely unrelated to the coronary anomaly and eventually subsided spontaneously on 6 month follow-up.